(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
This study compared the implementation of STAD (Student Team Achievement Divisions) and MURDER (Mood-Understanding-Recall-Detect-Elaborate-Review) cooperative learning in terms of mathematical communication, critical thinking, and students’ prior knowledge. Subjects were 49 tenth grader in one of vocational high schools in Bandung District, 23 students for STAD class and 26 for MURDER. Mathematical communication and critical thinking ability were evaluated from pretest, posttest, and N-Gain. Data were analyzed using t-test and one-way ANOVA. Difference in implementation results according to students’ prior knowledge was evaluated using scheffe test. Statistical analysis suggested that N-Gain difference in mathematical ability (p = 0,405, p> 0,05) as well as mathematical critical thinking (p = 0,667, p > 0,05) was insignificant between cooperative learning type. Students’ prior knowledge effect on these cooperative learning implementation results was addressed. Penelitian ini membandingkan penerapan pembelajaran kooperatif tipe STAD (Student Team Achievement Divisions) dengan pembelajaran kooperatif tipe MURDER (Mood-Understanding-Recall-Detect-Elaborate-Review) ditinjau dari kemampuan komunikasi, berpikir matematis, dan Pengetahuan Awal siswa (PAM). Subjek penelitian adalah 49 siswa kelas X di salah satu SMK di Kabupaten Bandung, 23 siswa untuk kelas STAD dan 26 siswa untuk kelas MURDER. Kemampuan komunikasi dan berpikir kritis dievaluasi dari hasil pretes, postes dan N-Gain. Data dianalisis menggunakan uji t dan anova satu jalur. Untuk mengetahui perbedaan hasil penerapan kedua pembelajaran kooperatif berdasarkan Pengetahuan Awal Matematis siswa (PAM) uji scheffe digunakan sebagai sebagai uji lanjutan. Hasil statistik menunjukkan bahwa tidak terdapat perbedaan N-Gain kemampuan komunikasi matematis (p = 0,405, p> 0,05) dan peningkatan kemampuan berpikir kritis matematis (p = 0,667, p > 0,05) antar tipe pembelajaran kooperatif. Pengaruh PAM terhadap hasil penerapan kedua pembelajaran kooperatif kemudian dibahas.